Pelatihan Tari Dolalak sebagai Upaya Pemenuhan Children Subjective Well Being pada Anak-Anak di Desa Awu-Awu, Kecamatan Ngombol, Kabupaten Purworejo - Adinda Putri; Faiz Rahmatullah Nugroho; Susilo Andi Darma (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
Tari Dolalak is a traditional folk art from Purworejo that incorporates a blend of dance movements, musical accompaniment, and choral singing. It can be performed by both men and women, either in groups or as pairs. The Universitas Gadjah Mada Community Empowerment Learning Team (KKN-PPM UGM) discovered that the youngsters of Awu-Awu State Elementary School (SDN) expressed a keen interest in learning and practicing Tari Dolalak. Nevertheless, there are restrictions on accessing it due to the school's lack of organised extracurricular activities. Consequently, the team endeavoured to address the children's requirements by collaborating with Tut Wuri Dance Studio, as dance is a means of self-expression and has the potential to impact an individual's subjective well-being. This study employs descriptive qualitative methodologies and utilises descriptive analysis to examine the data, specifically focusing on the various aspects of Children Subjective Well Being. These aspects encompass positive emotions, negative emotions, satisfaction with specific subjects, and overall life satisfaction. Tari Dolalak serves as a medium for children to comprehend positive and negative emotions, including happiness, comfort, courage to perform, sadness, disappointment, and anger. This enables them to cultivate supportive and communicative relationships with their peers, trainers, and the UGM KKN-PPM team. Additionally, dance training empowers children to identify and explore their needs and interests.